Inovasi Pengolahan Daun Jambu Biji: Pelatihan Dan Pemberdayaan Ekonomi Masyarakat - Hartati, Yeni; Alfajar, Muhammad Imam; Fitrah, Muhammad Idza Al; Susanti, Neri; Putri, Lidya Gustina (Jurnal Dehasen Mengabdi, 2024)
This research aims to utilize guava leaves, which are rich in bioactive compounds, in making tea as a strategy for economic empowerment of communities in Bengkulu Province. This program involves direct community training in planning, production, and marketing of guava leaf tea. The research sample consisted of residents from five villages in Bengkulu Province, namely Cawang Lama Village, Batu Kalung, Pondok Kelapa, Tanjung Agung, and Air Cool, including around 350 participants who were actively involved in the training. This program integrates material selection, processing, packaging and product innovation. The results show that people not only gain new knowledge and skills but also open up economic opportunities through selling tea products that meet SNI standards. The novelty of this research lies in the development of a guava leaf tea product that is traditionally underutilized, offering sustainable economic and health opportunities for rural communities. This program successfully utilizes local natural resources to create high value-added products that offer significant health benefits and economic potential.